Analysis of dermoscopic images of 101 patients with scabies - Zhou LIU; Wen LUO; Ao HUANG (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2023)
Objective To summarize and analyze the dermoscopic features of scabies. Methods Dermoscopic images of 101 patients with scabies were collected from the dermatology clinic from January 2022 to April 2023, and the microscopic features were analyzed. Results The burrows were visible in all cases (100%). Triangular structure in coffee color and brown dotted structure were observed in 97 cases (96.04%) and 10 cases (9.90%), respectively. Eight patients (7.92%) had "gray-edged line" sign and 2 cases (1.98%) showed a gray-white structure in the middle of burrow. Light-brown and dark-red transparent mites were found in 4 cases (3.96%) and 1 case (0.99%), respectively. Conclusions The characteristics of scabies under a dermoscope include burrows and coffee-colored triangular structure. Other non-specific structures, such as brown dots, "gray-edged line" sign and gray-white structure in the center of burrows, are also helpful for the dermoscopic diagnosis of scabies.